(untitled) (Transport systems and technologies, 2021)
The analysis of power steering which used on modern rolling stock is carried out. Their main shortcomings are identified. Given the requirements for the steering of trolleybuses, a solution to increase its efficiency is proposed. Based on the developed mathematical model and functional diagrams of the trolleybus steering system with a electric power steering based on rolling rotor switched reluctance motor, a simulation model of trolleybus steering was created using the Matlab Simulink package. The peculiarity of the simulation model is taking into account the mass and size characteristics of the rolling stock, the parameters of the suspension of the steered axle, the impact of the road surface and the speed of the trolleybus, changes in the parameters of the electric motor magnetic system during operation. The rolling rotor switched reluctance motor which is offered for use as the electric power steering of the LAZ E183D1 trolleybus is calculated. The calculation of the magnetic system of the engine by the finite element method with the subsequent approximation of the obtained results is carried out. With the help of the developed simulation model the simulation of the trolleybus steering system with electric power steering based on rolling rotor switched reluctance motor was performed. Time diagrams of transients in the trolleybus steering system are obtained and their processing and analysis are carried out.